The long-term effects of stress: role of miRNAs in the development of vulnerable and resilient phenotype. (September 2021) - Mazzelli, M.; Cattane, N.; Begni, V.; Papp, M.; Riva, M.A.; Cattaneo, A.
Abstract : Introduction: Only a proportion of individuals exposed to early in life adversities develops altered behaviours: while resilient individuals can develop adaptive responses for proper coping, vulnerable ones express inappropriate responses that can lead to psychopathology. A possible mechanism that could explain the long-term effects of early-life stress is represented by epigenetic. Methods: I used the animal model of stress represented by the Chronic Mild Stress (CMS) paradigm. A miRNomic analysis was performed in the ventral hippocampus of 6 controls, 6 vulnerable and 6 resilient rats and the raw data were processed for bioinformatic analysis. Results: In ventral hippocampus, a list of 21 miRNAs differentially modulated between Vulnerable vs Resilient rats were observed (FC>â"‚1, 2â"‚, p<0, 05). The pathway analysis showed the modulation of systems involved in neuronal development and function (Neurotrophin signalling pathway) and also in the regulation of inflammatory and stress response (FoxO signalling pathway). Conclusion: The vulnerable phenotype was associated with modulations in biological signatures involved neuronal function and stress/inflammatory response in Vulnerable rats that are not observed in resilient animals.